1999
DOI: 10.1046/j.1365-2036.1999.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

On demand therapy with omeprazole for the long‐term management of patients with heartburn without oesophagitis—a placebo‐controlled randomized trial

Abstract: Approximately 50% of patients with heartburn who do not have oesophagitis need acid inhibitory therapy in addition to antacid medication to maintain a normal quality of life. On-demand therapy with omeprazole 20 mg, is an effective treatment strategy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
2
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(159 citation statements)
references
References 22 publications
7
144
2
6
Order By: Relevance
“…However, in cases in which treatment was continued for at least six or more months after four or eight weeks of first-line treatment, both endoscopic and symptomatic remission rates were found to be higher than in the group not receiving treatment. In the study by Lind et al (22), higher symptomatic remission rates were detected at the end of the 6 th month in patients using 20 mg/day or 10 mg/day omeprazole during 6 months of maintenance treatment after first-line treatment compared to the placebo group (83%, 70%, and 56%, respectively). Similarly, higher symptomatic remission rates were found in cases using rabeprazole at the treatment dose for 6 months after first-line treatment than in the cases receiving placebo during maintenance treatment (86.7% vs. 74.9%, p<0.02) (23).…”
Section: Cessation Of the Treatment In Patients With Gerdmentioning
confidence: 99%
“…However, in cases in which treatment was continued for at least six or more months after four or eight weeks of first-line treatment, both endoscopic and symptomatic remission rates were found to be higher than in the group not receiving treatment. In the study by Lind et al (22), higher symptomatic remission rates were detected at the end of the 6 th month in patients using 20 mg/day or 10 mg/day omeprazole during 6 months of maintenance treatment after first-line treatment compared to the placebo group (83%, 70%, and 56%, respectively). Similarly, higher symptomatic remission rates were found in cases using rabeprazole at the treatment dose for 6 months after first-line treatment than in the cases receiving placebo during maintenance treatment (86.7% vs. 74.9%, p<0.02) (23).…”
Section: Cessation Of the Treatment In Patients With Gerdmentioning
confidence: 99%
“…9 There is increasing support for the on-demand approach as the preferred strategy. [10][11][12] For example, Bardhan et al prospectively enrolled 526 patients and treated them with either an H 2 RA or proton pump inhibitor taken as needed. 10 Approximately 50% of the patients did not need to take any acid-suppressive medication for a minimum of 6 of the 12 months of the study.…”
Section: Choice Of Strategymentioning
confidence: 99%
“…However, like functional heartburn, one cannot differentiate among any of the phenotypic presentations of GERD and heartburn-related functional esophageal disorders, using patients' severity, frequency, or duration of heartburn symptoms. 27 Overlap symptoms with other functional bowel disorders, GERD and psychological comorbidity are not uncommon. 5,28 A recent study suggested that anxiety may be more common in reflux hypersensitivity patients as compared with functional heartburn patients.…”
Section: Clinical Presentationmentioning
confidence: 99%